Monitoring of Surface Damage in Rails After Long Term Cyclic Loading - Katarina Zgutova; Juraj Sramek; Miroslav Neslusan; Peter Danisovic; Jiri Capek (Communications - Scientific letters of the University of Zilina, 2017)
This paper reports about possible concept in which surface damage of the rail after long tem cyclic loading can be executed. This study employs non destructive magnetic Barkhausen noise as a promising technique which exhibits very good sensitivity against extent of surface damage. Magnetic Barkhausen noise is correlated with the conventional parameters of surface integrity expressed in term of the thickness of damaged layer, its micro hardness as well as stress state. Furthermore, phase analysis of the real surface indicates that extensive phase transformations are produced by the repeated severe plastic deformation. Phase composition of the damaged layer indicates that structure transformation in the rail surface is thermally induced rather than deformation induced process